The Challenges of Reducing the Public Service Size and Enhancing Good Governance: The Case of Fiji - Peni Sikivou (Asia-Pacific Journal of Public Policy, 2023)
Fiji’s public sector has experienced over 30 years of reforms following the adoption of structural reforms in the late 1980s.  Despite three coup d’états in 1987, 2000 and 2006, the Fiji Government has continued to roll out the implementation of its public service reform program focusing on a reduction in the size of its public service with the adoption of the principles and practices of New Public Management (NPM).  This paper posits the question whether a reduction in the size of Fiji’s public service has been achieved using the recommended indicators by the International Monetary Fund (IMF). It then reviews the challenges faced by the Fiji public service in implementing key elements of NPM. Finally, it addresses the question whether Fiji’s public policy lens should remain focused on reducing the size on the public service and should policy efforts be concentrated on enhancing good governance practices within Fiji’s public service.